A preliminary investigation into the morphology of oral papillae and denticles of blue sharks (Prionace glauca) with inferences about its functional significance across life stages - Rangel, Bianca de S.; Wosnick, Natascha; Hammerschlag, Neil; Ciena, Adriano P. [UNESP]; Kfoury Junior, Jose Roberto; Rici, Rose E. G. (Wiley-Blackwell, 2017)
Sensory organs in elasmobranchs (sharks, skates, rays) detect and respond to a different set of biotic and/or abiotic stimuli, through sight, smell, taste, hearing, mechanoreception and electroreception. Although gustation is crucial for survival and essential for growth, mobility, and maintenance of neural activity and the proper functioning of the immune system, comparatively little is known about this sensory system in elasmobranchs. Here we present a preliminary investigation into the structural and dimensional characteristics of the oral papillae and denticles found in the oropharyngeal cavity of the blue shark (Prionace glauca) during embryonic development through adulthood. Samples were obtained from the dorsal and ventral surface of the oropharyngeal cavity collected from embryos at different development stages as well as from adults. Our results suggest that development of papillae occurs early in ontogeny, before the formation of the oral denticles. The diameter of oral papillae gradually increases during development, starting from 25m in stage I embryos, to 110m in stage IV embryos and 272-300m in adults. Embryos exhibit papillae at early developmental stages, suggesting that these structures may be important during early in life. The highest density of papillae was observed in the maxillary and mandibular valve regions, possibly related to the ability to identify, capture and process prey. The oral denticles were observed only in the final embryonic stage as well as in adults. Accordingly, we suggest that oral denticles likely aid in ram ventilation (through reducing the hydrodynamic drag), to protect papillae from injury during prey consumption and assist in the retention and consumption of prey (through adhesion), since these processes are only necessary after birth.
Keywords: embryonic development; feeding behavior; gustation; oropharyngeal cavity; ram ventilation